UTILIZATION OF SARDINES - MADHAVAN, P.; NAIR, T. S. UNNIKRISHNAN (Fishery Technology, 2016)
Oil sardine Sardinella longiceps stands out as the singlelargest pelagic fishery in India contributing to about 30% oftotal marine fish landings. Commensurate with the volume ofthe fishery, efforts at proper utilization of the fish by processinginto canned and frozen products or by distributing in fresh stateto internal consuming centres by quick transport have remainedrather very poor. The paper presents the problems and prospectswith regard to the utilization of the fish on the above lines.Results of investigations made at CÂ· I. F. T. on the utilization ofsardine body oil into industrially useful products such as factice,vehicle for paints, additive in lubricating oil and base for printingink have also been discussed.